2013
DOI: 10.1016/j.labeco.2013.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Gender wage gaps, ‘sticky floors’ and ‘glass ceilings’ in Europe

Abstract: We consider and attempt to understand the gender wage gap across 26 European countries, using 2007 data from the European Union Statistics on Income and Living Conditions.# The size of the gender wage gap varies considerably across countries, definitions of the gap, and selection-correction mechanisms. Most of the gap cannot be explained by the characteristics available in this data set. Quantile regressions show that, in a number of countries, the wage gap is wider at the top ('glass ceilings') and/or at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
204
2
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(254 citation statements)
references
References 37 publications
18
204
2
9
Order By: Relevance
“…This result is common across several papers (e.g. Christofides et al 2013;Mussida and Picchio 2014b;Piazzalunga and Di Tommaso 2016), which found an unexplained gender gap of about 10-11% (without self-selection correction) up to 14-18% (with self-selection correction). However, although those researches control for the level of education and broad categories of occupations and 4 professions, they do not control for the college major, which is likely to explain a proportion of the remaining wage gap.…”
Section: Italian Contextsupporting
confidence: 75%
See 2 more Smart Citations
“…This result is common across several papers (e.g. Christofides et al 2013;Mussida and Picchio 2014b;Piazzalunga and Di Tommaso 2016), which found an unexplained gender gap of about 10-11% (without self-selection correction) up to 14-18% (with self-selection correction). However, although those researches control for the level of education and broad categories of occupations and 4 professions, they do not control for the college major, which is likely to explain a proportion of the remaining wage gap.…”
Section: Italian Contextsupporting
confidence: 75%
“…Both the availability of childcare and of part-time can be considered as factors favouring work-family reconciliation, as studies on their impacts on employment show (Del Boca 2002;Brilli et al 2016). Reconciling work and family, they can have a positive effect on women's wages, increasing women attachment to the firm and their investment in firm-specific skills (Christofides et al 2013;Triventi 2013). Interestingly, these findings are confirmed when both variables are included in a unique regression.…”
Section: Regional Differences Institutional Setting and Social Normsmentioning
confidence: 90%
See 1 more Smart Citation
“…Prior research has shown that women advance at slower rates in their careers than men and found evidence for the sticky floors phenomenon (Baert et al, 2016;Biagetti & Scicchitano, 2011;Bjerk, 2008;Blau & Devaro, 2007;Christofides et al, 2013;Manning & Swaffield, 2008). At the same time, scholars increasingly emphasize the role of preferences to explain the career patterns of women and men (Azmat & Petrongolo, 2014;Bertrand, 2011 gender career gaps is correct, then gender differences in preferences should also result in a difference in the extent to which men and women want to be promoted.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Despite this, more than one half of the wage gap stays unexplained. An estimate of the unexplained part of the gender pay gap for European countries is presented in the studies of Beblo et al (2003) and Christofi des, Polycarpou and Vrachimis (2013). Diff erences in the characteristics of men and women explain only a small part of the gender pay gap in EU countries, if any.…”
Section: Introductionmentioning
confidence: 99%